2015
DOI: 10.1080/15548627.2015.1086522
|View full text |Cite
|
Sign up to set email alerts
|

RAB24 facilitates clearance of autophagic compartments during basal conditions

Abstract: RAB24 belongs to a family of small GTPases and has been implicated to function in autophagy. Here we confirm the intracellular localization of RAB24 to autophagic vacuoles with immuno electron microscopy and cell fractionation, and show that prenylation and guanine nucleotide binding are necessary for the targeting of RAB24 to autophagic compartments. Further, we show that RAB24 plays a role in the maturation and/or clearance of autophagic compartments under nutrient-rich conditions, but not during short amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 41 publications
1
31
1
Order By: Relevance
“…1995 RAB24: A small GTPase with unusual characteristics that associates with autophagic vacuoles and is needed for the clearance of autolysosomes under basal conditions. 1996,1997 RAB32: A small GTPase that localizes to the ER, and enhances autophagosome formation under basal conditions. 1998 RAB33B: A small GTPase of the medial Golgi complex that binds ATG16L1 and plays a role in autophagosome maturation by regulating fusion with lysosomes.…”
Section: Glossarymentioning
confidence: 99%
“…1995 RAB24: A small GTPase with unusual characteristics that associates with autophagic vacuoles and is needed for the clearance of autolysosomes under basal conditions. 1996,1997 RAB32: A small GTPase that localizes to the ER, and enhances autophagosome formation under basal conditions. 1998 RAB33B: A small GTPase of the medial Golgi complex that binds ATG16L1 and plays a role in autophagosome maturation by regulating fusion with lysosomes.…”
Section: Glossarymentioning
confidence: 99%
“…9 Overexpression of mutant HTT (huntingtin) protein with an expanded polyQ repeat in a defective RAB24 background leads to the accumulation of polyglutamine aggregates in HeLa cells. 8 Thus, it would be safe to conclude that RAB24 not only plays a role in basal autophagy, but also helps in clearing the protein load through autophagy, thereby highlighting its importance in post-mitotic cell types, such as neurons. Supporting this finding was the genetic study of canine heredity ataxia that ascribed mutations in RAB24 to be a cause of the disease.…”
Section: Rab-regulated Autophagy In Neuronal Survivalmentioning
confidence: 99%
“…7 Recent studies have elegantly shown the role of RAB24 in autophagic clearance. 8 Through the use of electron microscopy, it was suggested that it is not during the formation of the autophagosome that RAB24 plays a role. In fact, an early study had hinted at its role in maturation of autophagosomes as they reported the presence of RAB24 on late endocytic compartments.…”
Section: Rab-regulated Autophagy In Neuronal Survivalmentioning
confidence: 99%
“…Other studies carried out with the drs gene product suggest that drs interacts with Rab24 in the autophagosome and that it may regulate the fusion of autophagosomes with lysosomes . The participation of Rab24 in the final stages of autophagy was recently demonstrated in HeLa cells under nutrient‐rich conditions, showing the relevance of this rab during the clearance of the degradative autophagic compartments …”
Section: Discussionmentioning
confidence: 95%
“…31 The participation of Rab24 in the final stages of autophagy was recently demonstrated in HeLa cells under nutrient-rich conditions, showing the relevance of this rab during the clearance of the degradative autophagic compartments. 32 Considering the scanty information about the role of Rab24 in vesicle trafficking, we analyzed the function of this Rab in endosome maturation in a K562 cell model. The K562 is a chronic myeloid leukemia cell line that has long been used as a substrate to perform studies on vesicle trafficking, Rabs 33-36 and autophagy.…”
Section: Discussionmentioning
confidence: 99%